PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA INDUSTRI KERAJINAN PATUNG - I Gede Rihayana; Putu Pradiva Putra Salain; Nyoman Resa Adhika (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2022)
Human resources are an important factor in an organization. Every organization will also always improve the quality of its resources so that its performance is satisfactory. The quality improvement is also one of the efforts to make employees more motivated and clear the direction of the goals to be achieved. This study aims to determine the effect of transformational leadership on employee performance and the effect of communication on employee performance in the sculpture industry. The research data collection method was carried out by distributing questionnaires using a five-point Likert scale as a measuring tool. The population of this study were all employees in the sculpture industry with a total sample of 86 people. Sampling was done by using the saturated sample technique. Then the data were analyzed using SPSS 22.0 for Windows. The results show that transformational leadership and communication have a positive and significant effect on employee performance in the sculpture industry